2023
DOI: 10.2174/1871527321666220707111344
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis and Vitamin D Serum Levels: A Systematic Review and Meta-analysis

Abstract: Background: Vitamin D has been extensively studied for its role in immune modulation, especially in the process of tolerance induction. The loss of tolerance towards self-antigens is the basis of several autoimmune disorders, this seems to be related to lower levels of Vitamin D. A neurological autoimmune disorder due to the loss of tolerance to compounds at the neuromuscular junction is known as Myasthenia Gravis (MG). Objective: To assess the possible correlation between altered Vitamin D levels and MG. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A mounting body of evidence has demonstrated that Tregs are functionally defective in patients with MG, emphasizing their pivotal role in immune regulation. Recent studies in healthy individuals have supported the hypothesized immune-regulating impact of vitamin D, which is believed to be connected to increased regulatory T cells [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mounting body of evidence has demonstrated that Tregs are functionally defective in patients with MG, emphasizing their pivotal role in immune regulation. Recent studies in healthy individuals have supported the hypothesized immune-regulating impact of vitamin D, which is believed to be connected to increased regulatory T cells [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is associated with various chronic autoimmune diseases such as multiple sclerosis (MS) [7], systemic lupus erythematosus (SLE) [8], and rheumatoid arthritis (RA) [9]. Recent studies and systematic reviews have demonstrated significantly lower plasma 25(OH)D levels in patients with MG relative to healthy controls, suggesting the importance of monitoring 25(OH)D levels in MG patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, vitamin D may have immunomodulatory properties, which increases tolerance to autoantigens ( 33 ). A recent meta-analysis suggests that serum vitamin D levels are significantly lower in MG patients than in healthy controls ( 34 ). It is therefore possible that vitamin D deficiency may play a role in the development of autoimmune diseases like MG.…”
Section: Discussionmentioning
confidence: 99%
“…6.6.1. Micronutrients-Roles, Levels, Administration: Current Knowledge Significantly lower plasmatic concentrations of 25-OH vitamin D were observed in patients with MG [56]. Moreover, lower levels in patients with myasthenic crisis were reported compared with those of patients with MG without myasthenic crisis.…”
Section: Myasthenia Gravismentioning
confidence: 98%